Barriers and facilitators to oral health care utilization in culturally and linguistically diverse mothers: a mixed methods systematic review protocol. Issue 3 (2nd March 2021) - Marcus, Kanchan; Balasubramanian, Madhan; Short, Stephanie; Sohn, Woosung
ABSTRACT: Objective: The objective of the review is to synthesize existing literature examining the barriers and facilitators to preventive oral health care utilization experienced by culturally and linguistically diverse mothers. Introduction: Preventive oral health care in the absence of pain is underutilized in culturally and linguistically diverse groups. Culturally and linguistically diverse mothers experience oral health care utilization barriers compared to their host country counterparts. Much of the current evidence is focused on oral health care knowledge, attitudes, and beliefs of culturally and linguistically diverse groups. To date, it remains unclear as to which barriers or facilitators impact preventive oral health care utilization in culturally and linguistically diverse mothers. Inclusion criteria: This review will consider studies that explore oral health care utilization in culturally and linguistically diverse mothers (with children younger than 18 years) who are either born in a different country or who have one parent born in a country that differs culturally and/or linguistically to the host population. Papers that explore barriers and facilitators to oral health care utilization will be included. Quantitative and qualitative studies will be included. Methods: A three-step search strategy will be conducted within the following databases: MEDLINE, CINAHL, Web of Science, Cochrane Database of Systematic Reviews, ProQuest Central, and Scopus. The search will be supplemented with gray literature and reference searching from collected articles. No date limitation will be applied. Two reviewers will assess papers against the inclusion criteria. A convergent integrated approach using the JBI mixed methods methodology will be followed for critical appraisal, data extraction, and data synthesis and integration.